HUBUNGAN PIJAT ENDORPIN TERHADAP PRODUKSI ASI PADA IBU NIFAS DI PMB E BUKIT CIMANGGU BOGOR TAHUN 2023 - Azis, Aninditya (Journal of Midwifery Tiara Bunda, 2023)
Background: Many problems arise on the first day of breastfeeding such as breast milk does not come out so the baby does not get adequate milk, one of the efforts to increase the adequacy of breastmilk is a massage of oxytocin. Based on the results of preliminary studies conducted by researchers with interviews with 10 postpartum mothers where 7 puerpermothers said breast milk does not come out smoothly and do not know the massage oxytocin, while 3 postpartum said he had heard the oxytocin massage. Purpose: This study aims to analyze the effect of oxytocin massage on breastfeeding adequacy in postpartum in PMB Nani Area Sawangan District. Methods: This type of research is pre experimental with one group pretest-posttest design. The population of this study were all postpartum women in PMB Nani Area. Research sample of 32 puerperal mothers, taken by purposive sampling. The independent variable is the oxytocin massage and the dependent variable is the adequacy of breast milk. The research instrument used questionnaire. Data processing using editing, coding, tabulating and Chi-square statistical test. Result: The result of the research showed that before the massage of oxytocin, most of the postpartum women had enough milk, 11 respondents (36,7%) and most of the respondents had sufficient milk after oxytocin massage 19 respondents (63,3%). Chi- square statistical test showed that the significant value p value = 0.001 <α (0.05), so that Ha accepted. Conclusion:The conclusion of this research is the effect of oxytocin massage on breastfeeding adequacy in postpartum in PMB N Area Sawangan District.